ANALISIS PERBANDINGAN RISIKO DAN TINGKAT PENGEMBALIAN REKSADANA SYARIAH DAN REKSADANA KONVENSIONAL - Suhardi, -; Gani, Abdul (Journal of Accountancy FE UBB, 2013)
This study aims to determine risk calculation and rate of return PNM Amanah Sharia and PNM Dana Sejahtera II, and to provide empirical evidences that there are between the performance of sharia mutual fund and sharia index (JII index), between the performance of conventional mutual fund and conventional index LQ45 index), and also between the performance of sharia mutual fund and conventional mutual fund. It applies descriptive method with comparative study, and uses statistical analysis such as independent sample t-test, paired sample t-rest, and simple regression analysis to rest the hypotheses. Data is in the form of net asset value per unit of participation (NAV/unit), Combined Stock Price Index (IHSG), Jakarta Islamic Index (JII), daily LQ45 Index ,the interest rate of Bank Indonesia Certificates (SBI), and Wadiah Certificate of Bank Indonesia (SWBI) or Certificate of Bank Indonesia sharia (SBIS).            The results of the first hypothesis shows that from 2008 to 2010 the average of return of sharia mutual fund and JII sharia index is identical or similar, but the average of risk of those variables is vice versa. Second hypothesis yields that from 2008 to 2010 the average of return of conventional mutual fund and conventional LQ45 index is identical or similar, but the average of risk of conventional mutual fund and conventional LQ45 index is vice versa. While, the third hypothesis results from 2008 to 2010 the average of return and risk of sharia mutual fund and conventional mutual fund is identical or similar except in 2010, the average of risk of the variables is not identical or similar. Based on Sharpe index figures, Treynor index, and Jensen Index, the third hypothesis indicates that the performance of sharia mutual fund is better than the performance of conventional mutual fund. Then, through Jensen model this hypothesis also yields the performance of sharia mutual fund is better than the market performance and the conventional mutual fund so that it can be concluded the higher the excess of market return, the higher the excess of return of mutual fund portfolio and vice versa, by assuming the other variables are constant. Key words   : sharia Mutual Fund, Conventional Mutual Fund, sharia Index (JII Index), Conventional Index (LQ45 Index).